2003
DOI: 10.1051/0004-6361:20030902
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mercury-like orbits: A numerical study

Abstract: Abstract. The orbital evolution of ∼30 000 objects has been studied numerically for time scales of up to 11 Myr in order to investigate the dynamical importance of Mercury on objects with orbits similar to the planet's, as well as the existence of stable hermeocentric orbits. We find that Mercury, despite its small mass, exhibits a strong dynamical influence on objects with heliocentric Mercury-like orbits. The orbits of such objects may become temporarily and repeatedly Trojan-like for durations exceeding 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…These results are consistent with those obtained by Gladman (2003) for slightly different initial conditions. Warrel et al (2003) found that hermeocentric and 1:1 Mercury mean motion resonance orbits can be stable for long time periods, but that ejecta with velocities only slightly greater than the escape velocity are likely to be reaccreted due to the necessity of successive close encounters with Mercury to achieve significant gravitational scattering. They did not, however, provide a numerical result.…”
Section: Collision Time and Gravitational Scatteringmentioning
confidence: 99%
“…These results are consistent with those obtained by Gladman (2003) for slightly different initial conditions. Warrel et al (2003) found that hermeocentric and 1:1 Mercury mean motion resonance orbits can be stable for long time periods, but that ejecta with velocities only slightly greater than the escape velocity are likely to be reaccreted due to the necessity of successive close encounters with Mercury to achieve significant gravitational scattering. They did not, however, provide a numerical result.…”
Section: Collision Time and Gravitational Scatteringmentioning
confidence: 99%
“…Mercury could have its own Trojan asteroids, though they would last only 20 kyr (Warell et al 2003) and does have its own magnetic field, for reasons that remain under discussion (Aharonson et al 2004, who have resurrected a fossil field). It used to have a chaotic relationship between its orbital and rotation periods, from which the 3 : 2 resonance was captured (Correia & Laskar 2004).…”
Section: The Major Planetsmentioning
confidence: 99%
“…From the foregoing, therefore, it may be argued that there are at least two good reasons why the solar system might have supported a primordial population of Vulcanoid asteroids -either as the result of direct planetesimal growth, or via the destruction of two or more closely-packed planets. To these scenarios we can additionally add the process of Hermian Trojan capture [23], as well as the inward evolution of cometary nuclei, near-Earth asteroids and assorted collisional ejecta from the outer solar system [24].…”
Section: A Brief Historical Introductionmentioning
confidence: 99%
“…That the Vulcanoid zone is far from being a dynamically inactive region of the solar system is evidenced by the fact that both asteroids and cometary nuclei are regularly observed to pass through its borders in the modern era [23]. A search of the JPL Small-Body database, for example, reveals that at the present epoch there are 244 asteroids that cross the orbit of Mercury with perihelion distances located within the Vulcanoid zone.…”
Section: A Brief Historical Introductionmentioning
confidence: 99%